Contrast agent and radiation dose reduction in abdominal CT by a combination of low tube voltage and advanced image reconstruction algorithms - Buls, Nico (Eur Radiol, 2014)
OBJECTIVES: To assess image quality in abdominal CT at low tube voltage combined with two types of iterative reconstruction (IR) at four reduced contrast agent dose levels. METHODS: Minipigs were scanned with standard 320 mg I/mL contrast concentration at 120 kVp, and with reduced formulations of 120, 170, 220 and 270 mg I/mL at 80 kVp with IR. Image quality was assessed by CT value, dose normalized contrast and signal to noise ratio (CNRD and SNRD) in the arterial and venous phases. Qualitative analysis was included by expert reading. RESULTS: Protocols with 170 mg I/mL or higher showed equal or superior CT values: aorta (278–468 HU versus 314 HU); portal vein (205–273 HU versus 208 HU); liver parenchyma (122–146 HU versus 115 HU). In the aorta, all 170 mg I/mL protocols or higher yielded equal or superior CNRD (15.0–28.0 versus 13.7). In liver parenchyma, all study protocols resulted in higher SNRDs. Radiation dose could be reduced from standard CTDI(vol) = 7.8 mGy (6.2 mSv) to 7.6 mGy (5.2 mSv) with 170 mg I/mL. CONCLUSION: Combining 80 kVp with IR allows at least a 47 % contrast agent dose reduction and 16 % radiation dose reduction for images of comparable quality. KEY POINTS: • There is a balance between image quality, contrast dose and radiation dose. • Iterative reconstruction has a major, positive impact on this balance. • Both contrast dose and radiation dose can be reduced in abdominal CT. • The trade-off can be quantitatively described by a 3D model. • Contrast and radiation dose can be tailored according to specific safety concerns.